2015
DOI: 10.1007/s00268-015-2992-x
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative 11C‐Methionine PET/CT Enables Focussed Parathyroidectomy in MIBI‐SPECT Negative Parathyroid Adenoma

Abstract: Met-PET/CT raises the rate of correctly localized single parathyroid adenomas in patients with negative cUS and MIBI-SPECT/CT and increases the number of focussed surgical approaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(38 citation statements)
references
References 39 publications
(61 reference statements)
1
36
0
1
Order By: Relevance
“…[ 11 ] There have been a few reports for the use of 11 C-methionine PET as a promising imaging modality for localizing parathyroid adenomas. [ 12 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 11 ] There have been a few reports for the use of 11 C-methionine PET as a promising imaging modality for localizing parathyroid adenomas. [ 12 ]…”
Section: Discussionmentioning
confidence: 99%
“…The results regarding the use of 11 C-methione have been predominantly positive, although the study by Hermann et al showed a lower sensitivity compared to US and SPECT [29,30]. One of the most recent studies by Lenschow et al investigated its use in six patients with negative SPECT-CT and was able to correctly localize the adenoma in 5/6 patients [31]. Also, 11 C-methionine has proven to be useful in patients with renal failure and negative sestamibi scanning [32].…”
Section: Spect-ct Before Usmentioning
confidence: 93%
“…The mean volume of detected abnormal glands has been reported as 3.5 cm 3 , while the mean volume of missed glands is 1.4 cm 3 [85, 86]. …”
Section: Diagnosis and Imagingmentioning
confidence: 99%